PERLINDUNGAN HUKUM TERHADAP KREDITUR ATAS PEMBATALAN SERTIPIKAT HAK MILIK YANG SEDANG DIBEBANI HAK TANGGUNGAN (STUDI PUTUSAN MAHKAMAH AGUNG, NOMOR 140/KTUN/2011) - BRANDO MICO SEMBIRING (PREMISE LAW JURNAL, 2015)
The cancellation of the right to land certificate which is being imposed by the collateral right by the decision of the Supreme Court No.140/K/TUN/2011 due to its procedural deficiency in its issuance and this will inflict loss to the creditor because the creditor will lose the object of the collateral of the debitor’s credit. The theory used in analyzing this cancellation of the right to land certificate being imposed by the collateral right by the decision of the Supreme Court No.140/K/TUN/2011 was based on the principles of legal protection developed by Satjipto Raharjo supported by the legal certainty developed by E. Utrecht, and the principles of the legal purpose developed by Van Apeldoorn. This normative juridical study was to analyze the decision of the Supreme Court No.140/K/TUN/2011 and related it to the regulation of legislation, legal documents, and the text books related to the formulation of research problems. The data for this study were obtained through inventorying the basic reason of the decision of the Supreme Court. The cancellation of the right to land certificate being imposed by the collateral right waived the object of the collateral right, but since the issuance of collateral right because of the credit agreement made by the creditor and the debtor, that even though the collateral right has been waived, it does not mean that all of the debtor’s credit or debt was paid off, because it is still bound by the credit agreement made by the creditor and debtor, and all of the debtor’s properties both movable and fixed properties, both available and will be available become the responsibility of all contracts. Keywords: Legal Protection, Cancelation of Right to Land Certificate, Guarantee of Collateral Right